Design and evaluation of nanostructured lipid carriers loaded with Salvia officinalis extract for Alzheimer's disease treatment - Markova, Elena; Taneska, Lea; Kostovska, Monika; Shalabalija, Dushko; Mihailova, Ljubica; Glavas Dodov, Marija; Makreski, Petre; Geskovski, Nikola; Petrushevska, Marija; N Taravari, Arben; Simonoska Crcarevska, Maja (Wiley, 2022)
Considering the potential of Salvia officinalis in prevention and treatment of Alzheimer's disease (AD), as well as the ability of nanostructured lipid carriers (NLC) to successfully deliver drug molecules across blood-brain barrier (BBB), the objective of this study was design, development, optimization and characterization of freeze-dried salvia officinalis extract (FSE) loaded NLC intended for intranasal administration. NLC were prepared by solvent evaporation method and the optimization was carried out using central composite design (CCD) of experiments. Further, the optimized formulation (NLCo) was coated either with chitosan (NLCc) or poloxamer (NLCp). Surface characterization of the particles demonstrated a spherical shape with smooth exterior. Particle size of optimal formulations after 0.45 μm pore size filtration ranged from 127 ± 0.68 nm to 140 ± 0.74 nm. The zeta potential was -25.6 ± 0.404 mV; 22.4 ± 1.106 mV and - 6.74 ± 0.609 mV for NLCo, NLCc, and NLCp, respectively. Differential scanning calorimetry (DSC) confirmed the formation of NLC whereas Fourier-transform infrared spectroscopy confirmed the FSE encapsulation into particles. All formulations showcased relatively high drug loading (>86.74 mcg FSE/mg solid lipid) and were characterized by prolonged and controlled release that followed Peppas-Sahlin in vitro release kinetic model. Protein adsorption studies revealed the lowest adsorption of the proteins onto NLCp (43.53 ± 0.07%) and highest protein adsorption onto NLCc (55.97 ± 0.75%) surface. The modified ORAC assay demonstrated higher antioxidative activity for NLCo (95.31 ± 1.86%) and NLCc (97.76 ± 4.00%) as compared to FSE (90.30 ± 1.53%). Results obtained from cell cultures tests pointed to the potential of prepared NLCs for FSE brain targeting and controlled release.